2003
DOI: 10.1038/sj.npp.1300301
|View full text |Cite
|
Sign up to set email alerts
|

Biological Basis of Sex Differences in the Propensity to Self-administer Cocaine

Abstract: Women are at greater risk for cocaine addiction than are men, and female rats similarly show a greater propensity to self-administer cocaine than do male rats. This could be due to the intrinsic sex differences in brain organization, to the activational effects of circulating gonadal hormones, or both. For example, estradiol enhances dopamine release in the striatum and nucleus accumbens, and facilitates the behavioral sensitization induced by repeated cocaine exposure. We report here that independent of circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
230
7
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 275 publications
(273 citation statements)
references
References 32 publications
30
230
7
2
Order By: Relevance
“…As described previously (Hu et al, 2004), on the scheduled testing day, animals received 0.1 ml of peanut oil (OVX group and OVX+E Pellet group) or 17 β-estradiol (E) treatment in 0.1 ml peanut oil (s.c.) 30 min before the self-administration testing session (doses are given below for the acute E treatment group). Daily 1-hour sessions of self-administration testing were given for five consecutive days followed by two days off for five weeks.…”
Section: Self-administrationmentioning
confidence: 99%
See 3 more Smart Citations
“…As described previously (Hu et al, 2004), on the scheduled testing day, animals received 0.1 ml of peanut oil (OVX group and OVX+E Pellet group) or 17 β-estradiol (E) treatment in 0.1 ml peanut oil (s.c.) 30 min before the self-administration testing session (doses are given below for the acute E treatment group). Daily 1-hour sessions of self-administration testing were given for five consecutive days followed by two days off for five weeks.…”
Section: Self-administrationmentioning
confidence: 99%
“…Female rats show greater behavioral sensitization after repeated cocaine injections than do male rats (Glick et al, 1984;van Haaren et al, 1991;Chin et al, 2002;Hu et al, 2003). They also acquire cocaine self-administration more readily than male rats (Lynch et al, 1999;Lynch et al, 2001;Carroll et al, 2002;Hu et al, 2004).…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Our laboratory and others have shown that indirect dopamine agonists like cocaine induce greater behavioral (Bowman and Kuhn, 1996;Walker et al, 2001a) and neuroendocrine (Walker et al, 2001b) effects in female than male rats. Female rats trained to self-administer cocaine on a progressive ratio schedule have higher break points than males (Roberts et al, 1987;Carroll et al, 2002), and acquisition, maintenance and reinstatement of cocaine self-administration are greater in female rats Carroll, 1999, 2000;Hu et al, 2004). However, Caine et al (2004) using a relatively hightraining dose of cocaine found that male rats acquired self-administration earlier than females.…”
Section: Introductionmentioning
confidence: 99%